Literasi informasi budaya komunitas perantau Banyumas di Bandung dalam pelestarian kesenian Banyumasan - Awaliyah, Shelpi Nur; Khadijah, Ute Lies Siti; Rukmana, Evi Nursanti; Anwar, Rully Khairul (Jurnal Informatio, 2025)
Cultural information literacy plays a crucial role in preserving traditional arts in the modern era, especially among diaspora communities. The Genta Sentramas community, as a prominent and actively engaged diaspora community in cultural activities, needs to possess a good understanding and skills in cultural information literacy. This study aims to identify the forms of cultural information literacy used by the Genta Sentramas community in promoting and preserving Banyumas traditional arts in the city of Bandung. This research employed a qualitative method. The purposive sampling technique was used with the criterion that the samples were members of the Genta Sentramas Community. The results of this study indicate that the cultural information literacy of the Genta Sentramas Community in preserving Banyumas culture is carried out through the utilization of information technology. This includes social media and digital platforms that allow this diaspora community to document and disseminate information about traditional arts, including Banyumas dance and music, to the younger generation and the wider community. Other forms include visits to local cultural heritage sites and conducting art workshops. Cultural information literacy not only facilitates information access but also encourages the community to take an active role in producing and promoting their cultural elements. Thus, cultural information literacy becomes a vital instrument in maintaining the sustainability of Banyumas traditional arts in diaspora and ensuring that cultural identity remains alive amidst the challenges of modernization.